2014
DOI: 10.1074/jbc.m114.603944
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Protein for Bacterial Flagella Formation FlgJ Functions as a β-N-Acetylglucosaminidase

Abstract: Background: FlgJ is required for flagella formation in Salmonella enterica. Results: The lytic activity of FlgJ was determined to be that of a ␤-N-acetylglucosaminidase using a novel assay. Conclusion: FlgJ is a hydrolase and not a lytic transglycosylase. Significance: This information is essential for the search and rational design of inhibitors that may serve as leads to a new class of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 54 publications
2
72
0
Order By: Relevance
“…Recently, a PG-lytic enzyme associated with the flagella, FlgJ, was shown to cleave peptidoglycan between GlcNAc and MurNAc saccharides, acting as an endospecific N-acetylglucosaminidase (56). Another study showed that Helicobacter pylori and Salmonella typhimurium required activity of housekeeping lytic transglycosylases for functionality of the flagella (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a PG-lytic enzyme associated with the flagella, FlgJ, was shown to cleave peptidoglycan between GlcNAc and MurNAc saccharides, acting as an endospecific N-acetylglucosaminidase (56). Another study showed that Helicobacter pylori and Salmonella typhimurium required activity of housekeeping lytic transglycosylases for functionality of the flagella (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…motility), but not flagella assembly (57). This work proposed a model in which the N-actelyglucosaminidase activity of FlgJ clears peptidoglycan to facilitate flagella assembly, and subsequently housekeeping (involved in cell growth and cell wall maintenance) lytic transglycosylases remodel the opening in the peptidoglycan, producing 1,6-anhydromuramoyl peptidoglycan ends that interact with MotB, the flagellar motor protein (56,57). Does the difference in structure (and likely activity) between type III-associated PG-lytic enzyme EtgA and the flagellar FlgJ somehow play a nuanced role in assembly of each system, or does it reflect a different evolutionary acquirement of a PG-lytic enzyme?…”
Section: Discussionmentioning
confidence: 99%
“…Reaction specificity of SltF. The heavy water assay previously developed by Herlihey et al (6) was used to identify the type of lytic activity that SltF from R. sphaeroides catalyzes. S. Typhimurium PG in 50 mM sodium phosphate buffer (pH 7.0), prepared in […”
Section: Resultsmentioning
confidence: 99%
“…During flagellum assembly, extensive modifications need to occur to the peptidoglycan (PG) sacculus to accommodate the insertion of the secretion apparatus, as well as to stabilize the function of this system by acting as an assembly scaffold (6,7). PG is a heteropolymer of glycan strands and peptide chains forming a rigid network (sacculus) that completely surrounds bacterial cells to maintain the integrity of their cytoplasmic membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation